Are you talking about the angles in a triangle? Your question is not clear. I'll assume you are talking about a triangle.
Angle 1 + Angle 2 + Angle 3 = 180°
4x + 15 + 2x + 16 + x = 180°
Solve for x to find Angle 3, which in this case is the value of x.
Could anyone help me out, it’s would mean a lot.
Answer:
[tex]x = 19[/tex]
Step-by-step explanation:
If two lines are perpendicular, they create 4 90° angles. Meaning, in this case, that m<DBC = 90 and m<DBA = 90.
We're given that m<DBE = 2x - 1 and that m<CBE = 5x - 42.
The sum of angles DBE and CBE = m<DBC = 90°
We can add the two angles and set it equal to 90 to find x
[tex]2x - 1 + 5x - 42 = 90\\7x - 43 = 90\\7x = 133\\x = \frac{133}{7} =19[/tex]
write a word phrase for -12t + 2
Answer:
Negative Twelve Times a Number Plus Two
Step-by-step explanation:
Rewrite the following without an exponent. (-2)^2
Answer:
(-2)(-2) or 4
Step-by-step explanation:
[tex](-2)^2=4[/tex]
What is an exponent?"It is the number of times a number is multiplied by itself. "
For given question,
We have been given a number [tex](-2)^2[/tex]
We need to write given number without exponent.
[tex](-2)^2\\=(-2)\times (-2)\\=4[/tex]
Therefore, [tex](-2)^2=4[/tex]
Learn more about exponent here:
https://brainly.com/question/12158740
#SPJ2
what is the answer to
6x + 7 = 13 + 7x
x = -6 is the solution to the equation 6x + 7 = 13 + 7x
To solve the equation 6x + 7 = 13 + 7x, you can follow these steps:
Group the x terms on one side and the constant terms on the other side:
6x - 7x = 13 - 7
Combine like terms:
-x = 6
Multiply both sides of the equation by -1 to isolate x:
-1*(-x) = -1*6
This simplifies to:
x = -6
Therefore, the solution to the equation 6x + 7 = 13 + 7x is x = -6.
Learn more about algebraic Expression here:
https://brainly.com/question/953809
#SPJ6
Lucinda has a pocketful of dimes and quarters with a value of $6.20. The number of dimes is 18 more than 3 times the number of quarters. How many dimes and how many quarters does Lucinda have?
Answer:
The number of dimes is 42 and the number of quarters is 8
Step-by-step explanation:
Let
x -----> the number of dimes
y -----> the number of quarters
Remember that
1 dime=$0.10
1 quarter=$0.25
we know that
0.10x+0.25y=6.20 -----> equation A
x=3y+18 ----> equation B
Solve the system by graphing
Remember that the solution is the intersection point both graphs
The solution is the point (42,8)
see the attached figure
therefore
The number of dimes is 42 and the number of quarters is 8
There are 42 dimes and 8 quarters
Further explanationThe two-variable linear equation is a linear equation that has 2 variables and the exponent is one
Can be stated in the form:
[tex] \large {\boxed {\bold {ax + bx = c}}} [/tex]
x, y = variable
In this equation system there are coefficients and variables whose solutions can use:
1. substitution 2. elimination 3. graph 4. mix
We can state the problem in the form of algebraic equations
Lucinda has a pocketful of dimes and quarters with a value of $ 6.20
we translate this sentence into Algebraic expressions:
dime = D = $ 0.10
quarter = Q = $ 0.25
Then the equation becomes:
0.1D + 0.25Q = 6.20The number of dimes is 18 more than 3 times the number of quarters
we translate this sentence into Algebraic expressions:
D = 18 + Q
D - 3Q = 18
We solve the two equations with substitution and elimination
1. elimination
0.1D + 0.25Q = 6.20 x 10
D - 3Q = 18 x 1
------------------------------------
D + 2Q = 62
D - 3Q = 18
----------------------------------- -
5.5Q = 44
Q = 8
2. substitution
D - 3Q = 18
D - 3.8 = 18
D - 24 = 18
D = 42
Learn more
6 squared divided by 2 (3) +4
brainly.com/question/376058
an algebraic expression
brainly.com/question/20988
brainly.com/question/2285423
Solve 2x2 - 7x - 15 = 0.
Answer:
-18
Step-by-step explanation:
Follow PEMDAS. So first you do 2x2=4 then 4-7x= -3-15= -18
Good evening ,
_______
Answer:
x’=5
x’’=(-3)/2
____________________
Step-by-step explanation:
Δ=(-7)²-4×(2)×(-15)=49+120=169
√Δ=√169=13
then
x’=(7+13)/4=20/4=5
x’’=(7-13)/4=(-6)/4=(-3)/2.
:)
−2 1/4=r−4/5
What is r?
Answer:
r = -29/20 or r = -1.45
Step-by-step explanation:
I believe you are saying that the equation is -2 1/4 = r - 4/5. If so, then I would solve it in this way:
-2 1/4 = r - 4/5
-9/4 = r - 4/5
-9/4 (20) = r (20) - 4/5 (20)
-45 = 20r - 16
20r = -29
r = -29/20
r = -1.45
Check:
-2 1/4 = r - 4/5
-9/4 = r - 4/5
-2.25 = r - 0.8
-2.25 = -1.45 - 0.8
-2.25 = -2.25
-9/4 = -9/4
The calculated value of variable r is r = -1.45.
What is equation?An equation is a mathematical statement that shows the equality between two expressions. It typically consists of variables, constants, and mathematical operations (e.g., addition, subtraction, multiplication, division) with an equal sign (=) in between.
To solve for r in the equation -21/4 = r - 4/5
Step 1: Add 4/5 to both sides of the equation to isolate r:
r = -2.25 + 4/5
Convert -2.25 to a fraction with a common denominator of 5:
r = (-11.25/5) + (4/5)
Add the fractions:
r = (-11.25 + 4)/5
Simplify:
r = -7.25/5
r = -1.45
So, r = -1.45.
Learn more about equation here
https://brainly.com/question/17145398
#SPJ3
4^3-(24divided6)+8=?
Answer:
68
Step-by-step explanation:
4^3-(24÷6)+8
4³-(4)+8= 68
PLEASE DO MARK ME AS BRAINLIEST IF MY ANSWER IS HELPFUL :)
Answer:
68
Step-by-step explanation:
[tex] {4}^{3} - (24 \div 6) + 8 = 64 - 4 + 8 = 60 + 8 = 68[/tex]
According to the Order of Operations [GEMS\BOMDAS\PEMDAS etc.], in this case, you deal with the grouping symbols first before anything else, then comes the exponents, and finally comes Subtraction & Addition from right to left [or left to right, if you know what you are doing correctly]. Doing all of these will give sixty-eight.
I am joyous to assist you anytime.
Anything helps ouuuuuu:)))))))))))
Answer:
In order for the average to equal 3,000 then the total attendance must equal 9,000.
Show 1 = 2,580
Show 2 = 2,920
2 show total = 5,500
Therefore, third show total must equal 9,000 minus 5,500 =
3,500
Double-Check
2,580 + 2,920 + 3,500 = 9,000
Step-by-step explanation:
a cookie recipe calls for 1 2/3 of sugar if you plan on changing the recipe to make it 2 1/2 times as much how many cups of sugar will you need
Pls show work
Answer:
[tex]4\frac{1}{6}\ cups[/tex]
Step-by-step explanation:
we know that
The recipe calls for 1 2/3 of sugar
To make 2 1/2 times the recipe
Multiply 2 1/2 by 1 2/3
Convert mixed numbers to an improper fraction
[tex]1\frac{2}{3}=\frac{1*3+2}{3}=\frac{5}{3}\ cups[/tex]
[tex]2\frac{1}{2}=\frac{2*2+1}{2}=\frac{5}{2}[/tex]
so
[tex]\frac{5}{2}(\frac{5}{3})=\frac{25}{6}\ cups[/tex]
Convert to mixed number
[tex]\frac{25}{6}=\frac{24}{6}+\frac{1}{6}=4\frac{1}{6}\ cups[/tex]
Final answer:
To find out how much sugar is needed for the new recipe that is 2 1/2 times as much, follow the three-step process.
Explanation:
To find the amount of sugar needed:
Calculate 1 2/3 cups of sugar is equal to 5/3 cups of sugar.
Multiply 5/3 by 2 1/2, which equals 25/6.
Convert 25/6 to a mixed number, which is 4 1/6 cups of sugar needed for the new recipe.
2. Hal forgot the number of people at the
basketball game. He does remember that
the number had four digits and a 3 in the
tens place. Write a number that Hal could
be thinking of
Answer:
Well there is a lot of different numbers he could be thinking of because we are only given 2 useful pieces of information: Four Digits, and, a 3 in the tens place (30).
.
This means that the other spaces could be any number.
.
If X represents a random number it would be XX3X.
.
Eg 1234
What are two ways you can represent the number 27 using the number 3?
Answer:
see explanation
Step-by-step explanation:
27 = 3 × 9 ← is one way
27 = 3³ ← is another way
The two (2) ways you can represent the number 27 using the number 3 are shown below.
In this exercise, you're required to represent the number 27 by using the number 3. This simply means that you will represent the number 27 in terms of 3.
First way;
Since 3 is a factor of 27, we would multiply it to get 27.
[tex]27 = 3 * 3 * 3[/tex]
Second way;
From the above, we can see that the product of 3 is equal to 27.
[tex]27 = 3^{3}[/tex]
Find more information: https://brainly.com/question/14549998
How do you reduce 16/72
Answer:
2/9
Step-by-step explanation:
16/72 = (8×2)/ (8×9)=2/9
Answer: 2/9
Step-by-step explanation:
Divide it by 2 and keep going until you can't anymore.
5cosx -2sin(x/2) +7=0
Help me to find x step by step
pls
Answer:
x = 180
Step-by-step explanation:
First, you need to know
1. Double-angle formula:
cos(2x) = [tex]cos^{2}x - sin^{2}x[/tex]
2. Pythagorean identity:
[tex]cos^{2}x + sin^{2}x = 1[/tex]
Back to your problem, replacing the variable by the above:
[tex]5cosx-sin\frac{x}{2}+7 = 0[/tex]
[tex]5(cos^{2}\frac{x}{2}-sin^{2}\frac{x}{2}) - 2sin\frac{x}{2} + 7 = 0[/tex] By Double-angle formula
[tex]5(1 - 2sin^{2}\frac{x}{2}) - 2sin\frac{x}{2} + 7 = 0[/tex] By Pythagorean identity
Given [tex]y = \frac{x}{2}[/tex]
[tex]5(1-2sin^{2}y) - 2siny + 7 = 0[/tex]
[tex]10sin^{2}y+2siny-12=0[/tex]
[tex]5sin^{2}y+siny-6=0[/tex]
[tex](5siny + 6)(siny - 1)=0[/tex], we know -1 < sinx < 1, for every x ∈ R
[tex]siny = 1, y =90 [/tex]
[tex]y = \frac{x}{2}[/tex]
[tex]x = 180[/tex]
the table includes points on a quadratic function used to model the shape of a hole for one support beam at a new building site
distance from holes center in feet (x) : -2,0,2
depth from level ground in feet (y) :
-6,-8,-6
how deep is the hole?
2ft
4ft
8ft
16ft
Answer:
Step-by-step explanation:
16 feet
Answer:
Option C.
Step-by-step explanation:
Let x be the distance from holes center in feet and y be the depth from level ground in feet.
The given table represents a quadratic functions.
x : -2 0 2
y : -6 -8 -6
The depth from level ground in feet is same at x=-2 and x=2 it means the hole is symmetric about the line x=0.
The value of a quadratic function is on its extreme at line of symmetry.
In the given function the line of symmetry is x=0. So, the depth of the hole is defined on x=0.
From the table it is clear that at x=0 the depth from level ground is 8 feet.
Therefore, the correct option is C.
[2+(-4)]+5-[(-11)x(-2)]-(-7)
Answer: -12
Step-by-step explanation:
[2+(-4)] becomes (2-4), or -2, and 5-[(-11)x(-2)]-(-7) becomes 5-22+7, so the entire thing is -2+5-22+7, so it is -12.
The given expression [2+(-4)]+5-[(-11)x(-2)]-(-7) simplifies to -12.
To simplify the given expression, we follow the order of operations (PEMDAS/BODMAS):
Step 1: Evaluate the innermost parentheses:
[2 + (-4)] + 5 - [(-11) x (-2)] - (-7)
[2 - 4] + 5 - [(-11) x (-2)] - (-7)
Step 2: Complete the operations inside the brackets:
[-2] + 5 - [22] - (-7)
Step 3: Simplify the subtraction and negation:
-2 + 5 - 22 + 7
Step 4: Perform addition and subtraction from left to right:
(5 - 2) - 22 + 7
3 - 22 + 7
Step 5: Continue performing addition and subtraction:
-19 + 7
Step 6: Final result:
-12
The expression simplifies to -12.
Learn more about expression here
https://brainly.com/question/20439967
#SPJ2
Deborah spends 1/5 of her consulting time writing grant proposa
her consulting time writing grant proposals. If she spends 48 hours per month
writing grant proposals, how much time does she spend on consulting work?
Deborah spends 240 hours per month on consulting work. This was calculated by understanding 48 hours is 1/5 of her time, and multiplying it by 5 to find the total hours.
Explanation:The subject of this question is mathematics, and it involves the concept of fractions to solve a real-world problem. Deborah spends 1/5, or 20% of her time, writing grant proposals. If she spends 48 hours per month on this task, 48 hours represents 1/5 of her total consulting time.
To find the total consulting time, we need to do these steps: divide 48 by 1 to get 48 (since 48 hours is the 1/5), then multiply 48 by 5 (the denominator of the fraction, which represents the whole).
So, 48 (hours) divided by 1 equals 48, and 48 multiplied by 5 equals 240. Therefore, Deborah spends 240 hours per month on consulting work.
Learn more about Fractions here:https://brainly.com/question/10354322
#SPJ12
Translate (N-5)*7 turn into verbal statement
(N-5)*7
The N-5 is in parenthesis, so this needs to be done first, then the multiplication is done.
To say this verbally:
Subtract five from N, then multiply by seven.
If x is not equal to zero, which expression is equivalent to this expression?
(Picture of problem shown)
The answer is NOT D.
Answer:
the answer is C
Step-by-step explanation:
You can solve this by changing everything to fractional powers. 4th root of x^3 can be written as x^3/4. Since you are dividing you will subtract their powers, so 3/4 - 1/12 will give you the power raised by x. You can rewrite to 9/12 - 1/12 to get 8/12 which will end up as x^2/3
I tried to answer the last time you asked but you closed the question haha, I hope you understand!
Factor out the coefficient of the variable in the expression 1/3b - 1/3
Answer:
[tex]\dfrac{1}{3} \left (\dfrac{1}{b} - 1 \right )[/tex]
Step-by-step explanation:
[tex]f(x) = \dfrac{1}{3b} - \dfrac{1}{3}[/tex]
1. Find the least common multiple of the denominators
The least common multiple of 3 and 3 is 3.
2. Factor out ⅓.
[tex]\dfrac{1}{3b} - \dfrac{1}{3} = \mathbf{\dfrac{1}{3} \left (\dfrac{1}{b} - 1 \right )}[/tex]
Find the domain of the function.
Answer:
{y|10 < y}; ○ y > 10
Step-by-step explanation:
Whenever you have a Rational-Radical function, the answer will ALWAYS result in greater than.
I am joyous to assist you anytime.
What is the circumference of a circle with an area of 50.24 cm²?
Use 3.14 for pi.
Enter your answer as a decimal in the box.
Answer:
What is the circumference of a circle with an area of 50.24 cm²?
Use 3.14 for pi.
Enter your answer as a decimal in the box.
25.12cm
Write in slope-intercept form an equation of the line that passes through the points (−5,−3) and (3,−11)
Slope intercept form is y=-x-8.
V = arh for h
Helppppppppp
Answer:
h = V / ar
Step-by-step explanation:
V = arh
arh = V (divide both sides by "ar" )
h = V / ar
Lyndi has started a home business
Please help me idk this
Answer:3.3
Step-by-step explanation:
You want to look at the 3.2 because the 2 in the hundredths place so you will round it up because 6 is higher than 5 so it will be 3.3
Rounded to the nearest hundredth is 3.26
If |z - 7| - 2 = 2, then z = -3 /amp; z = -11 true or false
Answer:
False
Step-by-step explanation:
The absolute value always returns a positive value, however the expression inside can be positive or negative, that is
Given
| z - 7 | - 2 = 2 ( add 2 to both sides )
| z - 7 | = 4, then
z - 7 = 4 OR - (z - 7) = 4
z = 4 + 7 = 11 OR
- z + 7 = 4
- z = 4 - 7 = - 3 ( multiply both sides by - 1 )
z = 3
As a check
z = 11
| 11 - 7 | - 2 = | 4 | - 2 = 4 - 2 = 2 ← True
z = 3
| 3 - 7 | - 2 = | - 4 | - 2 = 4 - 2 = 2 ← True
Hence z = 11 or z = 3 are the solutions
1/2 of what number is 7 times 3?
By setting up the question as an algebraic equation, 1/2 * x = 21, and solving for x, it's determined that half of 42 is equal to 21.
Explanation:The question we're looking to solve is: "1/2 of what number is 7 times 3?" First, let's understand that 7 times 3 equals 21. The question asks which number, when halved, gives us 21. This can easily be set up as an algebraic equation: 1/2 * x = 21, where x represents the number we're trying to find.
To solve for x, we first multiply both sides of the equation by 2 to get rid of the fraction (1/2). This leaves us with: x = 21 * 2. Therefore, x = 42. The number, when cut in half, that results in 21, is 42.
Lilly and Rose are playing a game. In the game, each player starts with 0 points and the player with the most points at the end wins. Lilly gains 5 points two times, loses 12 points/ and then gains 3 points. rose loses 3 points two times, loses 1 point, gains 6 points, and then gains 7 points.
A. write and evaluate an expression to find Lillys score.
B. write and evaluate an expression to find Roses score
C. Who won the game, and why?
Answer:
Rose wins the game, with 6 points over Lilly's 1 point.
Step-by-step explanation:
Let's find Lilly's score. In this example we will add together the gains first, so we wouldn't have to deal with negative numbers, and after, we subtract the losses of each person.
Lilly's points:
[tex]0 + 5 + 5 + 3 - 12 = 1[/tex]
Rose's points:
[tex]0 + 6 + 7 - 3 - 3 - 1 = 6[/tex]
Rose wins the game with a 5 point lead.
Lilly's score is 1 and Rose's score is 6. Therefore, Rose wins the game because 6 is greater than 1.
Explanation:To find Lilly and Rose's score, we will create and solve an expression that reflects each player's game moves.
A. Lilly's score:
Lilly gains 5 points two times, loses 12 points, and then gains 3 points. We can express this as (5*2) - 12 + 3. First, we multiply 5 by 2, which equals 10. Then, we subtract 12 from 10, which gives -2. Finally, we add 3 to -2, resulting in a final score of 1 for Lilly.
B. Rose's score:
Rose loses 3 points two times, loses 1 point, gains 6 points, and gains 7 points. We can write this as (-3*2) - 1 + 6 + 7. First, we multiply -3 by 2, which equals -6. Then, we subtract 1 from -6 yielding -7. After that, we add 6 to -7, getting -1. Lastly, we add 7 to -1, resulting in a final score of 6 for Rose.
C. Game result:
Rose won the game because her final score of 6 is higher than Lilly's final score of 1.
Learn more about Mathematical expression here:https://brainly.com/question/30350742
#SPJ3
slope 2, y-intercept at 0
Answer:
y = 2x
Step-by-step explanation:
This is what is known as direct variation.
I am joyous to assist you anytime.